Widespread shifts in bird migration phenology are decoupled from parallel shifts in morphology. Issue 10 (20th June 2021) - Zimova, Marketa; Willard, David E.; Winger, Benjamin M.; Weeks, Brian C.
Abstract: Advancements in phenology and changes in morphology, including body size reductions, are among the most commonly described responses to globally warming temperatures. Although these dynamics are routinely explored independently, the relationships among them and how their interactions facilitate or constrain adaptation to climate change are poorly understood. In migratory species, advancing phenology may impose selection on morphological traits to increase migration speed. Advancing spring phenology might also expose species to cooler temperatures during the breeding season, potentially mitigating the effect of a warming global environment on body size. We use a dataset of birds that died after colliding with buildings in Chicago, IL to test whether changes in migration phenology are related to documented declines in body size and increases in wing length in 52 North American migratory bird species between 1978 and 2016. For each species, we estimate temporal trends in morphology and changes in the timing of migration. We then test for associations between species‐specific rates of phenological and morphological changes while assessing the potential effects of migratory distance and breeding latitude. We show that spring migration through Chicago has advanced while the timing of fall migration has broadened as a result of early fall migrants advancing their migrations and late migrants delaying their migrations. Within species, we found that longer wing length was linked to earlier spring migration within years. However, we found no evidence that rates of phenological change across years, or migratory distance and breeding latitude, are predictive of rates of concurrent changes in morphological traits. These findings suggest that biotic responses to climate change are highly multidimensional and the extent to which those responses interact and influence adaptation to climate change requires careful examination. Abstract : This study represents a unique empirical assessment of a presumed connection between shifting phenology and morphology using >70, 000 museum specimens of 52 species of migratory birds collected during 1978–2016. The authors discovery that these axes of adaptation are apparently decoupled has broad implications for predicting future responses to climate change.